MEMS-based Pt film temperature sensor chip on silicon substrate. (27th September 2022) - Huang, Mi-Mi; Zhao, Li-Bo; Han, Xiang-Guang; Jia, Chen; Gao, Yi; Fan, Shu; Yang, Ping; Dong, Linxi; Jiang, Zhuang-De
Abstract: The thin film temperature sensor chip is fabricated with the Ti/Pt film layer on a silicon substrate by micro electromechanical systems technology. Using electron beam evaporation, 10 and 100 nm thick Ti/Pt films layers are fabricated. Then, the annealing experiments for the temperature sensor chip are carried out in air and vacuum at 400 °C–800 °C. The relationship between the resistance of temperature sensor chip and tested temperature in the range of −30 °C–150 °C is studied based on different annealing conditions, and its electrical characteristic parameters are evaluated including temperature coefficient of resistance (TCR), hysteresis and measuring precision. At the same time, the morphology and grain size of the Pt film layer are studied by x-ray diffractometer, atomic force microscope and scanning electron microscope. The changes of square resistance and internal stress are tested by four probes and stress analyser to analyze the performance of the temperature sensor chip. The testing experiments show that the electrical properties of the temperature sensor chip annealed in air are better than those in vacuum. Finally, the temperature sensor chip is fabricated with the optimal performance with the annealing temperature of 800 °C for 30 min in air. Compared with before annealing, TCR increased by 75.4% from 1790 to 3140 ppm K −1, hysteresis reached 0.2% FS and precision reached 0.32% FS.